Analisis Faktor Maternal Penyebab Stunting di UPTD Puskesmas Limo Kota Depok Tahun 2025 (Journal of Telenursing (JOTING), 2025)
This study aims to describe the relationship between maternal factors and the incidence of stunting at the Limo Depok Health Center. This research method is cross-sectional with a quantitative approach. The study results showed a relationship between maternal upper arm circumference and stunting with a p-value of 0.040 and a relationship between maternal weight gain and the incidence of stunting with a p-value of 0.036. In conclusion, the right way that health workers can prevent stunting is to provide education and screening as early as possible for pregnant women so that signs of chronic energy deficiency in toddlers can be identified. Keywords: Maternal Factors, Upper Arm Circumference, Stunting